2005
DOI: 10.1038/sj.sc.3101742
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous upper and lower extremity complex regional pain syndrome type I in tetraplegia

Abstract: Study design: Clinical case report. Objectives: To present the first case of incomplete tetraplegic spinal cord injury (SCI) in which complex regional pain syndrome (CRPS) type I was present in all four of the patient's extremities. Setting: Ankara Physical Medicine and Rehabilitation Education and Research Hospital, Ankara, Turkey. Methods: A 49-year-old man with incomplete tetraplegia (American Spinal Injury Association (ASIA) C) was admitted to our clinic for rehabilitation. According to the patient's histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In addition, the characteristics of capricious symptom, difficult diagnosis, and refractory of CRPS indicate the need for the matched graded multi-professional care. Some complementary treatments such as medications, transcutaneous electrical nerve stimulation ( Sutbeyaz et al, 2005 ; Anandkumar and Manivasagam, 2014 ; Bilgili et al, 2016 ), acupuncture ( Peng et al, 2018 ), and manual lymphatic drainage ( Duman et al, 2009 ), have also shown great effect to improve pain and oedema in combination with exercise therapy ( Melf-Marzi et al, 2022 ). Given the comprehensive search, we found a lack of sufficient high- quality clinical studies about CRPS to carry out deeper analyses, which is one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the characteristics of capricious symptom, difficult diagnosis, and refractory of CRPS indicate the need for the matched graded multi-professional care. Some complementary treatments such as medications, transcutaneous electrical nerve stimulation ( Sutbeyaz et al, 2005 ; Anandkumar and Manivasagam, 2014 ; Bilgili et al, 2016 ), acupuncture ( Peng et al, 2018 ), and manual lymphatic drainage ( Duman et al, 2009 ), have also shown great effect to improve pain and oedema in combination with exercise therapy ( Melf-Marzi et al, 2022 ). Given the comprehensive search, we found a lack of sufficient high- quality clinical studies about CRPS to carry out deeper analyses, which is one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies the effect of whirlpool was explained by that whirlpool bath treatment improves regional perfusion, and nutrition; with this the oxygenation to the tissues increases and the skin softens. So as a result, pain and edema reduces and range of motion improves [37,38]. In a study the effects of a warm whirlpool bath on pain and stiffness of 44 patients with chronic stroke induced knee OA were evaluated and whirlpool was found beneficial for patients with chronic stroke induced knee OA [39].…”
Section: Discussionmentioning
confidence: 99%
“…Whirlpool, a physiotherapy modality, is one treatment option 20 ) . Clinical studies have shown that whirlpool bath treatment improves regional perfusion, nutrition, and oxygen to the tissues, and softens the skin; as a result, it is used to reduce pain and edema in CRPS 21 , 22 ) . A previous study conducted of whirlpool treatment also revealed an analgesic effect 23 ) .…”
Section: Discussionmentioning
confidence: 99%